Greenhouse economics : value and ethics - Spash, Clive L. (London ; New York : Routledge, 2002)
This important book examines one of the most crucial issues in the modern world: climate change. Providing a refreshing interdisciplinary perspective, which pulls together strands of natural science, economics and ethics. it also examines issues such as the intergovernmental panel on climate change reports, recent economic analyses and ethical concerns in economics.
Includes bibliographical references and index.
nmn, 08/08/16
Loan
Keywords: Environmental economics; Climatic changes; Greenhouse effect, Atmospheric